FY2012-FY2014 Medium-Term Budget. (Policy Papers; Policy Paper ;, 2011)
With the global financial landscape still unsettled, temporary spending looks set to remain at current levels over the next few years. Lending commitments and crisis-management activities have surged since the onset of the crisis: by the end of December 2010, there were 60 program and financial arrangements in place, compared with 40 at the time of the Fund's restructuring in early 2008. The higher lending has generated a sharp but temporary rise in income, but has also required an increase in temporary spending. This expenditure will unwind over time, but only marginally over the FY 12-14 MTB period.